Fuzzy logic controlled SPMSM drives for long cable applications - Cheok, Yong Seng (2014)
In many industrial Variable Speed Drives (VSD) applications require that the Voltage Source Pulse Width Modulation (PWM) Inverter and the motor be at separate locations, often resulting in long motor leads, high voltage oscillation at the motor terminal, increase harmonics content and affect the overall motor speed performance. To our knowledge, a detailed investigation of the impact of various cable lengths over speed response has not been reported in the literature. Therefore, the research focuses on investigation and evaluation of the performance of a Vector Controlled Sinusoidal Permanent Magnet Synchronous Motor (SPMSM) drive, controlled by PI speed controller and FL speed controller for different cable lengths conditions. Current control is performed in the stationary reference frame, using hysteresis current controllers. The scope of research is focusing on low speed operation based on simplified 9 rules Fuzzy Logic speed controller and tested for tested 100 meter maximum cable lengths and 1.1kW SPMSM. The drive is modeled, simulated and implemented using MATLAB, SIMULINK and FUZZY LOGIC Toolboxes. The experimental study is carried out based on dSPACE hardware platform for validating the simulation results. PI and Fuzzy Logic speed controllers are designed and tuned to obtain the best performance with criteria less than 0.72% overshoot and ±0.1 steady state error are acceptable. All the controller parameters are fixed based on designed case study for overall simulation and experimental studies. The overshoot/undershoot, settling time and rise time of the speed response are used to evaluate the controller performance. The simulation and experimental results have showed that the speed response and load rejection are degraded due to variation in cable length and increase of motor inertia. The proposed Fuzzy Logic has demonstrated better performance in term of step speed command, load rejection capability and THD compare with the results obtained from PI speed controller for different cable length conditions. The THD of the three-phase stator current is increased when motor is connected with longer cable. Fuzzy Logic speed controller shows better THD of stator currents as compare to PI speed controller where the THD was remain constant even cable length was increasing. When switching frequency of the Hysteresis PWM is increased, the stator currents will be closer to sinusoidal and indirectly reduced the %THD of the drives. Study on variable speed drive performance versus different cable length can be further investigated for medium and high motor speed commands operation.